Educação Popular em Saúde e infâncias: Uma análise das produções nacionais sobre práticas educativas e de cuidado - Poiatti, Gabriela Gonçalves (Universidade Federal de São Carlos, 2025)
This study analyzes national productions on Popular Education in Health (EPS) in the context of childhood, highlighting the potentials and challenges of this practice in Brazil. Based on the principles of Paulo Freire, EPS aims to promote a humanized, dialogical, and participatory approach to healthcare. The objective was to identify and analyze scientific articles on the application of EPS with children, seeking care practices and the development of inclusive public policies. The methodology adopted was a narrative literature review, selecting open-access articles published in the last 20 years, through searches in Scielo, BVS, and the CAPES Periodicals Portal. The research identified a lack of studies focused on children, particularly at the intersection with EPS. The results indicate that EPS practices for childhood are still underexplored, with more emphasis on adult and social vulnerability contexts. Furthermore, the studies highlight the need for robust institutional and political support for the implementation of these practices. The final considerations emphasize the importance of strengthening EPS public policies, aiming for the integration of various sectors and the creation of care spaces that respect children's uniqueness and rights, with a focus on expanding research on the topic.
Popular Education in Health and childhood: An analysis of national productions on educational and care practices
Keywords: Educação Popular; Saúde; Criança; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL; 3. Saúde e Bem-Estar